Nutrient allocation among stem, leaf and inflorescence of jatropha plants - Rosiane L. S. de Lima; Hans R. Gheyi; Carlos A. V. de Azevedo; Valdinei Sofiatti; Genelicio S. Carvalho; Jairo O. Cazetta (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Information on the partitioning of nutrients among various organs in jatropha plants, as a complementary tool for the recommendation of fertilization, is still not available. This study aimed to evaluate the contents of macro and micronutrients in stems, leaves and inflorescences of jatropha branches at the beginning of flowering. At the beginning of flowering, adult jatropha plants were sampled and divided into five compartments: inflorescences, leaves from vegetative branches, leaves from flowering branches, stems from vegetative branches and stems from flowering branches. Jatropha inflorescences are a drain of nutrients. Leaves are important sources of nutrients demanded by the inflorescences at the beginning of flowering. The higher allocation of nutrients in the inflorescences suggests the need for preventive/corrective fertilizations, which must be performed at least 30 days before flowering, providing plants with nutrients in adequate amounts for a good yield.